The marine-derived fungus Tinctoporellus sp CBMAI 1061 degrades the dye Remazol Brilliant Blue R producing anthraquinones and unique tremulane sesquiterpenes - Rodriguez, Julie P. G.; Williams, David. E.; Sabater, Isadora D.; Bonugli-Santos, Rafaela C.; Sette, Lara D. [UNESP]; Andersen, Raymond J.; Berlinck, Roberto G. S. (Royal Soc Chemistry, 2015)
Degradation of the dye Remazol Brilliant Blue R (RBBR) by the marine-derived fungus Tinctoporellus sp. CBMAI 1061 led to the formation of four unprecedented anthraquinones, of which two were halogenated. Investigation of the RBBR degradation medium also led to the isolation of three new tremulene terpenes, of which two bear novel 2-hydroxy- or 2-methoxy-3,4-dihydro-2H-pyrrole N-oxide moieties. The products of RBBR degradation and of the fungus metabolism have been identified by analysis of spectroscopic data.